Application of a Multi-Gas Detector for Monitoring Gas Composition in Minced Beef During Storage - Aleksandar Veličković; Lorenzo Cocola; Massimo Fedel; Bojana Danilović; Massimo De Marchi; Luca Poletto; Dragiša Savić (Foods)
This study aims to assess the capability of using a specially designed device to monitor changes in gas concentration (CO2, NH3, H2S, and O2) in the atmosphere above the minced beef meat, during storage at refrigerated temperature. With its array of sensing channels, the multi-gas detector device facilitates the detection of precise gas concentrations in sensitive environments, enabling the monitoring of various processes occurring within stored meat. To delve into the connection between microbial activity and gas emissions during storage, fluctuations in microbial populations in the meat were observed, focusing on prevalent meat microbiota such as lactic acid bacteria (LAB) and Enterobacteriaceae. A significant reduction of O2 content in the stored samples was observed after seven days (p < 0.05), while a significant release of CO2 was detected on the fourth day of storage. Significant changes (p < 0.05) in the gas content were tracked until the 11th day of storage followed by intensive microbial growth. NH3 and H2S levels remained undetectable throughout the experiment. The results showed a correlation between an increase in gas content in the headspace and an increase in the number of LAB and Enterobacteriaceae in meat. Modern multi-gas detector devices can indirectly determine microbial contamination in closed meat packaging.